Lack of Association of MFN2 (rs1474868) Gene Polymorphism with Essential Hypertension in South Indian Population - Jayaseelan, Vijayashree Priyadharsini; Muthusamy, Karthikeyan; Venkatramani, Shridevi; Arumugam, Paramasivam; Gopalswamy, Jayaraman; Thiagarajan, SanthiyaSathiyavedu (Asian Journal of Biological and Life Sciences, 2016)
Essential hypertension (EH) is the most common condition which contributes to ~ 95% of cases and has no clear identifiable basis. Although, EH has a strong genetic basis, the identification of genes associated with it has been difficult to achieve because of the complexity of regulation of blood pressure, its multifactorial nature and the presence of multiple susceptibility genes that have profound environmental and gene–gene interactions. A case-control association study was conducted to investigate the possible involvement of MFN2 (rs1474868) polymorphism in essential hypertensive patients. A total of 568 cases and 604 controls were recruited for this study. The SNP marker of MFN2 gene (rs1474868) did not show any significant difference between the case and control groups in south Indian population studied. The genotype frequency was almost the same for both the case and control data sets. The result of the present study indicates that MFN2 polymorphism is not associated with essential hypertension in south Indian population.
Keywords: Essential hypertension; HSG; MFN2; PCR-RFLP; SNP